An urgent need to understand and address the safety and well‐being of hospital "sitters". Issue 12 (9th September 2015) - Schoenfisch, Ashley L.; Pompeii, Lisa A.; Lipscomb, Hester J.; Smith, Claudia D.; Upadhyaya, Mudita; Dement, John M.
Abstract : Background: Hospital sitters provide continuous observation of patients at risk of harming themselves or others. Little is known about sitters' occupational safety and well‐being, including experiences with patient/visitor‐perpetrated violence (type II). Methods: Data from surveys, focus groups, individual interviews at six U.S. hospitals were used to characterize the prevalence of and circumstance surrounding type II violence against sitters, as well as broader issues related to sitter use. Results: Sitter respondents had a high 12‐month prevalence of physical assault, physical threat, and verbal abuse compared to other workers in the hospital setting. Sitters and other staff indicated the need for clarification of sitters' roles regarding patient care and sitter well‐being (e.g., calling for assistance, taking lunch/restroom breaks), training of sitters in personal safety and de‐escalation, methods to communicate patient/visitor behaviors, and unit‐level support. Conclusions: The burden of type II violence against hospital sitters is concerning. Policies surrounding sitters' roles and violence prevention training are urgently needed. Am. J. Ind. Med. 58:1278–1287, 2015. © 2015 Wiley Periodicals, Inc.